Uncommon peritoneal anomaly of spleen associated with the unusual relationship of spleen with the left lobe of the liver. - Satheesha NB,; Srinivasa Rao S,; Narendra P,; Anitha G,; Surekha DS,; Naveen K,; Ashwini A,; Swamy RS, (Department of Surgery, UKM Medical Centre, 2013)
Though congenital anomalies of the spleen are quite common, the peritoneal anomalies of the spleen are very rare. In the present case, we observed two unusual phrenico-splenic ligaments connecting the spleen to the diaphragm. Apart from this, the left lobe of the liver was elongated and was related to the diaphragmatic surface of the spleen. The splenic artery had a straight course to the spleen, indicating the possible restricted movements of the spleen. Knowledge of such unusual relation of spleen is essentially important for the surgeons as the elongated left lobe of the liver might get ruptured in addition to the spleen in the fractures of the left 9th, 10th and 11th ribs. Awareness of the straight course of the splenic artery is also of importance to Radiologists performing arterial splenoportography.